COMPARISON OF KINETIC MODELS FOR BIOGAS PRODUCTION FROM RICE STRAW (Universitas Negeri Semarang, 2017)
The rising of global energy demand has led to an energy crisis, especially fossil energy. The development of renewable energies is needed to overcome the energy crisis. Biogas is one of renewable energies (biofuels) which is developed to minimize the dependency on fossil fuels. Biogas can be derived from agricultural wastes such as rice straw. The aim of this research was to compare the kinetic models of biogas production form rice straw using the linear and exponential equations models. This research was conducted at the total solid (TS) content of 20%, 22% and 24%. The result showed that the exponential equation had a better correlation than the linear equation on the ascending period of biogas production, while linear equation was better than exponential equation during descending period.